Development of Economic Mechanism for Ensuring Ecological Security in Kazakhstan - Igaliyeva, Laura; Yegemberdiyeva, Saule; Utepkaliyeva, Kansulu; Bakirbekova, Aigul (International Journal of Energy Economics and Policy, 2020)
This article deals with the analysis and assessment of the environmental situation in the regions of Kazakhstan, as well as issues of developing an economic mechanism for ensuring environmental safety in the country. The problem of ensuring environmental safety has acquired the status of one of the most priority and acute problems facing humanity. It is very difficult to simultaneously maintain the pace of economic growth and minimize the negative consequences of human impact on nature. Creating a reliable and effective mechanism is the main task of ensuring environmental safety in all states. It can provide a balanced solution to economic problems and problems of preserving the natural environment to meet the vital needs of the population. Based on the analysis of conceptual approaches to the formation of the economic mechanism for ensuring environmental safety, the fundamental principles of the formation of this mechanism in Kazakhstan have been determined. Keywords: Economic Mechanism, Environmental Safety, Sustainable Development, Environmental Pollution, Greening the Economy. JEL Classifications: O18, O21, O31, Q57 DOI: https://doi.org/10.32479/ijeep.9634